2017
DOI: 10.1111/his.13272
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of p53 and WT1 immunohistochemical expression patterns in tubo‐ovarian high‐grade serous carcinoma before and after neoadjuvant chemotherapy

Abstract: Immunohistochemical expression of p53 (abnormal/mutation-type pattern) and WT1 in HGSC is almost universal and is largely concordant before and after chemotherapy. This finding underscores the reliability of these diagnostic markers in small samples and in surgical samples following neoadjuvant chemotherapy, with very few exceptions. A novel finding was the significant diminution in intensity of WT1 staining following chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In this study, we confirmed the presence of TP53 mutations in HGSC showing a wild-type p53 immunostaining pattern and demonstrated the mutational constancy between matched pre-and post-chemotherapeutic HGSC tissue samples. This result is not only concordant with a previous study reporting pre-and post-chemotherapeutic p53 expression in HGSC using only immunohistochemistry (40), but also presents confirmatory evidence via NGS. Our data suggest that similar p53 immunoexpression patterns in preand post-chemotherapeutic samples indicate the presence of the same TP53 mutation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we confirmed the presence of TP53 mutations in HGSC showing a wild-type p53 immunostaining pattern and demonstrated the mutational constancy between matched pre-and post-chemotherapeutic HGSC tissue samples. This result is not only concordant with a previous study reporting pre-and post-chemotherapeutic p53 expression in HGSC using only immunohistochemistry (40), but also presents confirmatory evidence via NGS. Our data suggest that similar p53 immunoexpression patterns in preand post-chemotherapeutic samples indicate the presence of the same TP53 mutation.…”
Section: Discussionsupporting
confidence: 92%
“…Although a certain number of HGSC cases show wild-type pattern of p53 immunostaining, there have been a few studies showing that, when sequenced, all HGSC cases examined actually bear TP53 mutations (9,15). Considering that p53 immunopositivity is determined by an immunohistochemical staining pattern that correlates with TP53 mutation as opposed to simply a positive or negative staining and that some HGSC cases with truncating or splice site TP53 mutations can show a non-functional p53 expression pattern, the fact that p53 immunostaining cannot accurately predict TP53 mutational status is understandable (40,41). There are two main chemotherapeutic treatment methods for managing ovarian carcinomas, including HGSC: 1) PDS followed by postoperative platinum-based adjuvant chemotherapy and 2) neoadjuvant chemotherapy followed by IDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After constructing the tissue microarray, the samples were stained for O -GlcNAcylation (RL2) and OGT. The intensity of the staining was scored using the H-score method (3D HISTECH, H-SCORE = ∑(PI × I) = (percentage of cells of weak intensity × 1) + (percentage of cells of moderate intensity × 2) + (percentage of cells of strong intensity × 3) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that immunohistochemical expression of WT1 in HGSC is largely concordant before and after chemotherapy, although generalised diminution of nuclear immunoreactivity has been noted in post-treatment tumours 64. Diffuse immunoreactivity with p16 is usually seen in HGSC,65 66 and ER positivity is also commonly seen 67 68.…”
Section: Pathological Examination Of Post-nact Specimensmentioning
confidence: 99%